2017
DOI: 10.1016/j.jmu.2017.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Point-of-care-ultrasound (POCUS) to MRI for the Diagnosis of Medial Compartment Knee Injuries

Abstract: Background:Ultrasound has become an increasingly utilized tool for the imaging of the musculoskeletal system, especially for imaging the components of the knee. Even though MRI is touted as being the golden standard for identifying knee pathologies, the use of ultrasound has gained popularity in this field given its ability for rapid diagnosis. This study aims to investigate the efficacy of point-of-care ultrasound (POCUS) to diagnose injuries to the medial knee compartment when compared to magnetic resonance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 17 publications
2
34
3
Order By: Relevance
“…Radial tearing will cause more damage to peripheral fibrils running from the inner to outer surface [6,15,16,37,40]. MRI affords a 90-95% diagnostic success rate, although MRI data should be combined with clinical findings [12,44]. We showed a 35-year-old male patient with a degenerative horizontal tear of the medial meniscus rim of the left knee (Fig.…”
Section: Discussionmentioning
confidence: 89%
“…Radial tearing will cause more damage to peripheral fibrils running from the inner to outer surface [6,15,16,37,40]. MRI affords a 90-95% diagnostic success rate, although MRI data should be combined with clinical findings [12,44]. We showed a 35-year-old male patient with a degenerative horizontal tear of the medial meniscus rim of the left knee (Fig.…”
Section: Discussionmentioning
confidence: 89%
“…The most common system, according to Hughston and the American Medical Association (AMA), uses a three-point scale of medial gapping in 20-30° flexion of the knee [20,22]. Other classification systems differ with respect to clinical symptoms at different flexion angles and different valgus loads, which are highly examiner-dependent and make reliable comparison difficult [21,25,27,[31][32][33]42]. Hence, stress radiography, ultrasonography, and magnetic resonance imaging are supposed to help guide further treatment recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…There is some literature available for abdominal and pleural US on the non-inferiority of POCUS, but little in the Orthopedic realm [ 21 ]. A study by Ghosh et al has demonstrated higher positive and negative predictive values in diagnosing medial compartment knee injuries using POCUS when compared to MRI [ 22 ]. Nonetheless, future research comparing POCUS to the traditional US is needed to understand further the role of POCUS in the care of DDH.…”
Section: Discussionmentioning
confidence: 99%